The contribution of future orientation towards employability in students of vocational high school - Fatwa Tentama; Bella Rifqi Nabilah (Journal of Education and Learning (EduLearn), 2020)
The employability of students in vocational high schools is a major concern that must be considered. Employability as the ability and skills that will make it easier for individuals to get a job. Future orientation is one of the factors that can affect employability. This study aims to test the role of future orientation on student employability empirically. The population in this study were all students of class XII at Vocational High School Piri 1 Yogyakarta, totaling 150 students. The sample in this study amounted to 58 students and selected using cluster random sampling techniques. The research method used is a quantitative method with a scale of employability and a scale of future orientation. Analysis of the data used in this study is the product-moment analysis technique. The results of data analysis showed that there was a very significant positive correlation between future orientation towards employability with r = 0.636 and significance level (p) = 0.000 (p less than 0.01). Future orientation contributes 40.5% to employability, and the remaining 59.5% is influenced by other variables.